PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 20 PADANG - Sari, Maisyarah Ivo Permata (Pendidikan Matematika, 2014)
This research has problems from understanding of mathematic concept students thatstill low and most of students have not responsible to do some tasks that had beengiven by the teacher. This research has a purpose to know whether bisnis berisikotechniques have positive effect toward understanding concept of mathematicstudents on eighth grades at Junior High School 20 Padang.This research includesin pre-experimental with one shot case study design. This research takes populationall of 8 grades in SMPN 20 Padang which divided into 8 classes in 2014/2015academic year. This research use random sampling, and class VIII 7 had chosen asan experimental class. Instrument in this research takes final test that has indicatorunderstanding concept and give assessment based on analytical scoring rubric. Thistest that is used are essay test with reliability r11 = 0,888. This research analyze thedata based on t test two sides. Based on description and analyze the data, it can beseen that the development of studentâs understanding concept in mathematic areincreases in every meeting. And the value of hypothesis are calculated 3,705. avalue greater than of t-table is 2, 052. So, it can be conclude that applying BusinessTechniques have positive effect toward understanding of mathematic conceptstudents on 8 SMPN 20 Padang.